2021
DOI: 10.1108/ijhma-01-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

Comparing predictive performance of general regression neural network (GRNN) and hedonic regression model for factors affecting housing prices in “Pune-India”

Abstract: Purpose The purpose of this study is to compare the predictive performance of the hedonic multivariate regression model with the probabilistic neural network (PNN)-based general regression neural network (GRNN) model of housing prices in “Pune-India.” Design/methodology/approach Data on 211 properties across “Pune city-India” is collected. The price per square feet is considered as a dependent variable whereas distances from important landmarks such as railway station, fort, university, airport, hospital, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 86 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…In accounting for lower house prices near airports, a number of studies have reported higher noise levels as the main reason, namely, McCord et al (2018), Batóg et al (2019), Abhyankar and Singla (2022) and Zheng et al (2020). The study by McCord et al (2018), however, notes that the airport noise effect on house prices is insignificant at greater distances, suggesting a distance decay effect.…”
Section: Earlier Studiesmentioning
confidence: 99%
“…In accounting for lower house prices near airports, a number of studies have reported higher noise levels as the main reason, namely, McCord et al (2018), Batóg et al (2019), Abhyankar and Singla (2022) and Zheng et al (2020). The study by McCord et al (2018), however, notes that the airport noise effect on house prices is insignificant at greater distances, suggesting a distance decay effect.…”
Section: Earlier Studiesmentioning
confidence: 99%
“…e hidden Markov model is a tool that is utilized by some academics in order to model the emotional states of learning that students are experiencing, comprehend the Mobile Information Systems changes that students are experiencing in their emotional cognition, and adapt teaching strategies to fit the overall cognitive state of learners (HMM) [15,16,[22][23][24][25][26]. Personal recommendation and learning system adaptability research are currently in the early stages of weak artificial intelligence [27,28].…”
Section: Related Workmentioning
confidence: 99%
“…There is a strong correlation between the cost of a house and its geographical location [1]. The price of a house is related to the distance from important landmarks such as schools, subway stations and hospitals [7]. The distance to these important landmarks is positively related to the house price.…”
Section: Introductionmentioning
confidence: 99%
“…The distance to these important landmarks is positively related to the house price. The closer the distance, the higher the price [7]. Houses close to these important landmarks are more convenient for people's daily life.…”
Section: Introductionmentioning
confidence: 99%